(untitled) (VERITAS LEGIS JOURNAL, 2026)
The article examines the genesis and historical development of German constitutionalism as a significant phenomenon of European legal thought. Particular attention is devoted to the analysis of its doctrinal foundations, formed within the framework of the classical German legal and philosophical tradition. The evolution of constitutional and legal ideas, as well as their transformation into a coherent system of principles underlying the modern constitutional order, is explored. The study analyzes the works of prominent German thinkers, including Georg Wilhelm Friedrich Hegel, Ferdinand Lassalle, Karl Theodor Welcker, Robert von Mohl, and others, whose theoretical contributions laid the intellectual foundations of German constitutionalism. Their concepts substantiate key elements of constitutional theory, such as the principle of the rule of law, the organization of state authority, and the protection and safeguarding of human rights and freedoms. It is demonstrated that German constitutionalism developed as a consistent doctrinal system that exerted a significant influence on the evolution of the concept of the Rechtsstaat and on the formation of constitutional models in various countries. The study concludes that many of its principles have been adopted and adapted within modern legal systems. Particular significance is attributed to their role in shaping the constitutional order of the Republic of Kazakhstan, where the influence of the German legal tradition is clearly reflected.